Resistência da soja à Meloidogyne incognita : herança e marcador molecular - Oliveira, Leonardo Augusto de (2012)
Diseases, especially those caused by plant parasites nematode, are among the factors that limit the achievement of high yields in soybeans. The attack of nematodes, particularly the species Meloidogyne incognita and M. javanica, are widely spread and responsible for significant losses in soybean crops. The objective of this work was to study the inheritance of resistance to M. Incognita, and to identify microsatellite molecular markers promising for use in Marker Assisted Selection (MAS). Crosses were performed between cultivar BRS 133 (susceptible) and CD 201 (resistant). The phenotypic evaluation of F2:3 population was conducted in a greenhouse under controlled conditions. Plants were inoculated, and after thirty days were scored from 1 to 5 for each plant, depending on the number of galls formed on the roots. The results obtained were consistent with the hypothesis of three genes/QTL for resistance, being two dominant and one recessive. The parental varieties were evaluated with 384 markers, and 48 microsatellite loci were polymorphic. Extreme phenotypes for resistance and susceptibility ware analyzed with this markers. Twenty- three plants of each group (resistant and susceptible) were evaluated with each polymorphic marker, and the marker/QTL association was tested by regression analysis. The marker Satt358 was significantly associated with resistance to M. incognita when tested with the population of 129 F2:3 families. This marker explained 9.9% of resistance to this nematode in soybean. The results support the usefulness of the marker Satt358 on molecular marker-assisted selection for resistance to M. incognita.